A Critical Discourse Analysis on Antara English News Reports About Bullying in Education Institutions in Indonesia - Muhammad Firnas Hibatulloh; Dewi Nur Suci; Anggun Guna Puspita; Irza Fadhilatur Rohmah (ELITE Association Indonesia, 2023)
ABSTRACT Bullying of children in the school environment in Indonesia is still common. Online news channels become one of the shapers of public perception related to the cases that occur. One of them is Antara English, which is one of the online news channels that is read and trusted by many people because of its high credibility. This study aims to investigate Antara English representations on bullying victims to see whether Antara English, in its reporting, sided with certain parties or is neutral. This study uses Fairclough's three-dimensional framework of critical discourse analysis including description, interpretation, and explanation. Furthermore, for analyzing the linguistic properties, Halliday's systemic functional grammar will be applied in terms of transitivity and modality to get the ideational and interpersonal metafunction of the news reports. The data were taken from three news reports published in 2022. The result of the study showed that Antara English represemts bullying victim as the one who suffered and extremely impacted by the bullying. From the result, it is suggested that online news readers can be more critical in reading news reports in order to get the right interpretation of the news. Keywords: critical discourse analysis, systemic functional grammar, bullying, Antara English